The “National Political Elites” and the Disintegration of the SFRY, 1970 - 1991 - Obradovic, Marija; Novakovic, Nada (Advances in Social Sciences Research Journal, 2022)
The goal of this paper is research into the role of the "national polititical elites", religious and ethnic identies of the working class in the didintegration of the Socialist Federal Republic of Yugoslavia (SFRY) in 1991. The article is based on the hypothesis that the "national political elites" in Yugoslavia, in conditions marked by the process of the historical collapse of the socialist social-economic system in Eastern Europe, through the manipulation of power, i.e. by means of propaganda of nationalistic ideology, exploited the ethnic and religious identites of the working class in Yugoslavia and converted that political pover through war into economic power by the expropriation of public property. Therefore, relying on the historical method of economics, this paper analyses the process of the founding of the conservative "national political elites" from the League of Communist of Yugoslavia's nomenclature during the process of the elemental and uncontrolled borrowings of various Yugoslavian subjects on the international financial market in the period between 1970 and 1980 and the "debt crisis" during the 1980's. The second hypothesis researched is based on the political economy approsch that the basic cause for the disintegration of the SFRY were economic factors (international and local) and not ethnic conflicts.